Dynamics of proinflammatory (IL-1, TNF), immunoregulatory (IL-4), and anti-inflammatory (IL-10) cytokines in the various outcomes of abdominal fever development - D. B. Mirzajanova; N. G. Gulamov (Журнал инфектологии, 2020)
Dynamics of proinflammatory (IL-1, TNF), immunoregulatory (IL-4) and anti-inflammatory (IL-10) cytokine levels was studied in 35 and 6 patients with abdominal fever with outcome of the disease in recovery and acute bacterial carriage, respectively. Level of cytokines in peripheric blood was studied at the height of the disease (the second week) and at the stages of early (the fourth week) and late (before hospital discharge) convalescence. Control group included 24 healthy individuals. At the height of the disease IL-1 and TNF levels were significantly higher in patients with disease recovery compared to patients with acute bacterial carriage. Dynamics of indices of anti-inflammatory cytokines IL-4 and IL-10 in patients with acute abdominal fever with outome in recovery and acute bacterial carriage was similar: the indices were increased at the height of the disease, at the stages of early and late convalescence the stable tendency to further increase was observed. Dynamics of proinflammatory (IL-1 and TNF) cytokines demonstrates that chronization of infectious process in abdominal fever/development of acute bacterial carriage is specified by insufficient increase of proinflammatory cytokines.